Indeks Kuning Telur (IKT), Haugh Unit (HU) dan Bobot Telur pada Berbagai Itik Lokal di Jawa Tengah - Dwi Purwati; Muhammad Anwar Djaelani; Enny Yusuf Wachidah Yuniwarti (Jurnal Akademika Biologi, 2015)
Ducks is one of poultry producer eggs that potential in Indonesia. Research about ducks eggs quality which includes egg yolk index (IKT), haugh unit (HU) and eggs weight local ducks in central java very important to know the genetic ability to ducks from each region and as an attempt to provide and improve the quality of  foodstuffs. The purpose of the research was analyze eggs quality from local breeds in Central Java that is Tegal ducks, Magelang ducks and Pengging ducks, viewed from the value IKT, HU and weight eggs. Ducks used in this research are raised in the hall breeding and raising ducks satker non ruminant Banyubiru, Ambarawa. The research was done by measuring egg quality from each ducks that was six month. Data  were  analyzed using analysis of variance (ANOVA) with the differentiating factor is the type of ducks. If the data were analyzed significantly different, then do a further test using the Least Significant Differences Test (LSDt) at 95% confidence level. The results showed that ducks eggs Magelang has the heaviest weight  copared with Tegal ducks and Pengging ducks. Eggs quality data include IKT and HU showed no  significantly different from each ducks. The research conclusion the eggs Magelang ducks is the best eggs.   Keywords: Local Ducks Cental Java, Eggs Quality, IKT, HU, Egg Weight